Development and process evaluation of a motor activity program for people with profound intellectual and multiple disabilities - Helena J. M. van Alphen; Aly Waninge; Alexander E. M. G. Minnaert; Annette A. J. van der Putten (BMC, 2021)
Abstract Background The support of people with profound intellectual and multiple disabilities (PIMD) rarely focused on motor activity, which might have negative consequences for the quality of life of these people. Evidence-based motor activity programs that present individually tailored and structural motor activity for these people are, regretfully, lacking. This study developed such a program for these people and evaluated the implementation process. Methods The motor activity program is developed in accordance with the theoretical premises of the educational program and consists of four methodological steps in which the content is individually filled with: motor activity structurally embedded within the activities of daily living, and 3-5 motor activities aimed at a specific goal, which is evaluated. Program delivery consisted of a manual, explanation to the teams, and coaching of one contact person per participant (n = 9). Process evaluation included the delivered fidelity, dose, reach, and adaptations made during the program. In addition, mechanisms of impact and the influence of contextual factors were evaluated. Data collection included researcher logbooks, individual program content, and staff reports. Results The intended fidelity, dose, and reach were not obtained in most participants. Content has been made explicit for seven participants, but only in one participant all critical steps in implementation were performed as intended, though later in time. In three participants, previously offered motor activities were described within the weekly program, but without all activities having a clear link with the goal set. It is showed that the core elements of the program were affected with the conceived implementation plan. The time schedule, critical elements in implementation and program content were influenced by a lack of conditions such as professionals' motivation and responsibility, methodical working, interdisciplinarity and continuity in staff. Conclusions The results suggest that the implementation might be improved in case more attention is paid to the organizational conditions and implementation structure. The findings led to substantial changes in the implementation strategy. This study underlines the importance of process evaluation prior to testing for effectiveness. Trial registration The (overarching) study was registered at the Netherlands Trial Register (number 6627) on February 10, 2017: https://www.trialregister.nl/trial/6449 .